2021
DOI: 10.3389/fmed.2021.753821
|View full text |Cite
|
Sign up to set email alerts
|

Chest Imaging in the Diagnosis and Management of Pulmonary Tuberculosis: The Complementary Role of Thoraci Ultrasound

Abstract: Tuberculosis (TB) is a severe infectious disease that still represents a major cause of mortality and morbidity worldwide. For these reasons, clinicians and radiologists should use all the available diagnostic tools in the assessment of the disease in order to provide precise indications about starting an anti-tubercular treatment and reduce risk of TB transmission and complications especially in developing countries where the disease is still endemic. As TB mycobacteria are mainly transmitted through respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, our work underlines some advantages of LUS that are widely useful for radiologists and clinicians: it is widely available, is safer and cheaper compared with CT and can be easily performed in every hospital and health facility, in low- to middle-income countries as well [ 31 , 32 ]. Moreover, LUS does not require any patient transport because it is a bedside exam, nor does it require the presence of expensive CT scanners or dedicated technicians [ 33 , 34 , 35 ]. An interesting emerging field of study could be the introduction of new Artificial Intelligence (A.I.)…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our work underlines some advantages of LUS that are widely useful for radiologists and clinicians: it is widely available, is safer and cheaper compared with CT and can be easily performed in every hospital and health facility, in low- to middle-income countries as well [ 31 , 32 ]. Moreover, LUS does not require any patient transport because it is a bedside exam, nor does it require the presence of expensive CT scanners or dedicated technicians [ 33 , 34 , 35 ]. An interesting emerging field of study could be the introduction of new Artificial Intelligence (A.I.)…”
Section: Discussionmentioning
confidence: 99%
“…In 1992, Yang et al first used high-frequency, real-time sonography to determine the nature of pleural effusion. [13] Previously, most reported studies were performed using contact B-scans. [14][15][16] Yang et al analyzed sonographic images of 320 patients with pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…After comparing the limits and advantages of the method, they concluded that the use of LUS could have had a good rationale in circumstances that include avoiding exposure to ionizing radiation such as patients who need frequent follow-ups and in countries with limited resources. In fact, according to the authors there were still insufficient evidences to judge the diagnostic accuracy of LUS for a screening purpose in TB [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, subpleural nodule and lung consolidation were the lung ultrasound findings with the highest sensitivities, ranging from 72.5% to 100.0% and 46.7% to 80.4%, respectively. Only the study by Heuvelings et al [ 24 , 25 ] provided detailed data on LUS findings in pediatric PTB (consolidations were the most common parenchymal alteration in children and LUS sensitivity was 45.6% in their detection). The authors concluded that there was no consensus on the optimal protocols for acquiring and analyzing LUS images for PTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation